The surface texture book : more than 800 colour and texture samples for every surface, furnishing and finish. - Martin, Cat, ....- (London : Thames and Hudson, 2005)
Today's prevailing design aesthetic is minimalism: clean lines, uncluttered spaces, and simple but elegant materials. Rather than relying on bold fabrics and an overabundance of accessories, designers are allowing surfaces themselves to determine color, pattern, and texture. The perfect tool for this new approach is The Surface Texture Bible, which offers more than 800 samples for surfaces, furnishings, and finishes. The book is a comprehensive resource for choosing metals, glass, plaster, stone, wood, paper, cork, and many other materials to create visual interest in projects large and small. Appropriate for both amateur and professional interior designers, this handy guide features more than 250 pages of large-format color and texture swatches. Also included is essential advice on installing, maintaining, and cleaning finishes, information about product safety, and a list of email addresses for major international suppliers. With a spiral-bound, easy-to-use format, The Surface Texture Bible provides a virtual showroom where designers can go again and again to select just the right materials for every job.
Keywords: Materialen ; stoffen